Penegakan Hukum terhadap Pelaku Tindak Pidana Judi Online berdasarkan Teori Keadilan - Anugrah , Sandy Kelvin; Rahmat, Diding; Sudarto, Sudarto (LITERATUS, 2025)
Online gambling is a form of cybercrime that must be prevented and eradicated. Law enforcement efforts are needed so that this crime does not continue to develop. This study discusses the regulation of online gambling crimes based on legislation in Indonesia and its law enforcement based on the theory of justice. This study uses a normative legal research method. The results of the study show that online gambling in Indonesia is prohibited in Article 27 paragraph (2) of Law Number 1 of 2024, which includes acts of offering, providing opportunities, making it a livelihood, or being involved in gambling businesses. Violators of this provision can be subject to a maximum sentence of 10 years in prison and/or a maximum fine of IDR 10 billion in accordance with Article 45 paragraph (3) of Law 1/2024. In addition, gambling provisions are also regulated in Articles 303 and 303 bis of the Criminal Code and Articles 426 and 427 of the new Criminal Code (Law 1/2023). Law enforcement based on the theory of justice emphasizes the importance of a balance between the strictness of the law and respect for human dignity. It is hoped that there will be legal updates related to online gambling through the Criminal Code, legislation, government regulations, and ministerial regulations that are able to provide strict criminal sanctions but still pay attention to human rights.